Physical activity and sedentary activity: population epidemiology and concordance in Australian children aged 11–12 years and their parents. (4th July 2019) - Fraysse, François; Grobler, Anneke C; Muller, Josh; Wake, Melissa; Olds, Timothy
Abstract : Objectives: To describe the epidemiology and parent–child concordance of objectively measured physical activity in a population-based sample of Australian parent–child dyads. Design: Cross-sectional study (Child Health CheckPoint) nested within the Longitudinal Study of Australian Children. Setting: Assessment centres in seven Australian cities and eight regional towns or home visits; February 2015–March 2016. Participants: Of all CheckPoint families (n=1874), 1261 children (50% girls) and 1358 parent (88% mothers) provided objectively measured activity data, comprising 1077 parent–child dyads. Outcome measures: Activity behaviour was assessed by GENEActiv accelerometer. Duration of moderate-to-vigorous physical activity (MVPA) and vigorous physical activity and sedentary behaviour (SB) were derived using Cobra custom software, along with MVPA/SB fragmentation and mean daily activity. Pearson's correlation coefficients and linear regression estimated parent–child concordance. Survey weights and methods accounted for the complex sample design and clustering. Results: Although parents had average lower accelerometry counts than children (mean [SD] 209 [46] vs 284 [71] g.min), 93% of parents met MVPA daily duration guidelines on published cutpoints (mean [SD] 125 [63] min/day MVPA), compared with only 15% of children (mean 32 [27] min). Parents showed less daily SB duration (parents: 540 [101], children: 681 [69] minutes) and less fragmented accumulation of MVPA (parents: α=1.85, children: α=2.00). Parent–child correlation coefficients were 0.16 (95% CI 0.11 to 0.22) for MVPA duration, 0.10 (95% CI 0.04 to 0.16) for MVPA fragmentation, 0.16 (95% CI 0.11 to 0.22) for SB duration and 0.18 (95% CI 0.12 to 0.23) for SB fragmentation. Conclusions: Standardised cutpoints are needed for objective activity measures to inform activity guidelines across the lifecourse. This may reflect large amounts of time in non-shared environments (school and work).